The Relationship Between Language Anxiety and Students English Speaking Performance During Classroom Presentation at the Second Semester in English Department of UNIQHBA - Nolayatin; Sarwadi; Lalu Abdul Khalik; Abdul Wahab (HAMJAH DIHA FOUNDATION bekerjasama dengan PENA INSTITUTE, 2025)
The objective of this study is to examine the correlation between language anxiety and English language proficiency in the context of classroom presentation by second-semester students in the Department of English at UNIQHBA. This study employed a quantitative approach with correlational method to identify and elucidate the relationship and the level of correlation between students language anxiety and their speaking performance. The Foreign Language Classroom Anxiety Scale (FLCAS), developed by Horwitz et al., was employed to quantify students anxiety when speaking in English. Furthermore, students speaking performance was evaluated through a Speaking Assessment by Bown & Abeywickrama. The result of the analysis indicated a correlation (0.188) between language anxiety and students speaking performance. However, the correlation was not statistically significant, with a sig-(0,408) exceeding 0,05. Consequently, it can be concluded that the relationship between language anxiety and students English speaking performance among second-semester students in the department of English at UNIQHBA is very weak and insignificant.